A social justice policy framework for funding the acquisition of higher education qualifications in South Africa - Blackmur, D. J. (South African Journal of Higher Education, 2023)
Much of the recent published research on the future contribution of the South African university system to the development of a more just society offers an evaluative framework that contains two principal assertions: firstly, South African under-graduate university students must receive state subsidies from taxpayers; and, secondly, austerity, marketisation, credentialisation, commodification, and related neoliberal conceptions of education and society have hindered efforts to achieve a more just society. This article offers a dissenting analysis that is nevertheless located within a social justice framework. It argues that a student loan system of funding the production of university qualifications is consistent with Rawlsian principles of fairness in the distribution of income and wealth.